TAMI-38. CYSTEINE-PROMOTING COMPOUNDS INDUCE MITOCHONDRIAL TOXICITY IN GLIOBLASTOMA THROUGH ALTERED PYRUVATE AND SERINE METABOLISM. (9th November 2020) - Noch, Evan; Palma, Laura; Yim, Isaiah; Binder, Bhavneet; Benedetti, Elisa; Krumsiek, Jan; Elemento, Olivier; Cantley, Lewis
Abstract: Glioblastoma (GBM) remains a poorly treatable disease with high mortality. Tumor metabolism in GBM is a critical mechanism responsible for accelerated growth because of upregulation of glucose, amino acid, and fatty acid utilization. However, little is known about the metabolic alterations that are specific to GBM and that are targetable with FDA-approved compounds. To investigate tumor metabolism signatures unique to GBM, we interrogated the TCGA and a cancer metabolite database for alterations in glucose and amino acid signatures in GBM relative to other human cancers and relative to low-grade glioma. From these analyses, we found that GBM exhibits the highest levels of cysteine and methionine pathway gene expression of 32 human cancers and that GBM exhibits high levels of cysteine-related metabolites compared to low-grade gliomas. To study the role of cysteine in GBM pathogenesis, we treated patient-derived GBM cells with a variety of FDA-approved cyst(e)ine-promoting compounds in vitro, including N-acetylcysteine (NAC) and the cephalosporin antibiotic, Ceftriaxone (CTX), which induces cystine import through System Xc transporter upregulation. Cysteine-promoting compounds, including NAC and CTX, inhibit growth of GBM cells, which is exacerbated by glucose deprivation. This growth inhibition is associated with reduced mitochondrial metabolism, manifest by reduction in ATP, NADPH/NADP+ ratio, mitochondrial membrane potential, and oxygen consumption rate. Metabolic tracing experiments with 13 C6-glucose demonstrate that L-serine is rapidly depleted in GBM cells upon treatment with NAC and CTX, and exogenous serine rescues NAC- and CTX-mediated cell growth inhibition. In addition, these compounds reduce GBM mitochondrial pyruvate transport. We show that cysteine-promoting compounds reduce cell growth and induce mitochondrial toxicity in GBM, which may be due to rapid serine depletion and reduced mitochondrial pyruvate transport. This metabolic phenotype is exacerbated by glucose deprivation. This pathway is targetable with FDA-approved cysteine-promoting compounds and could synergize with glucose-lowering treatments, including the ketogenic diet, for GBM.